Mommies Pink Book: Rekod Kesihatan Ibu Digital - Ihsan, Amirah Humaira; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2025)
The Mommies Pink Book System addresses the challenges faced by traditional maternal healthcare record-keeping methods, such as manual systems prone to errors, limited accessibility, and physical book deterioration. This project proposes a digital solution to revolutionize maternal health records, emphasizing the shift from conventional practices to an Electronic Health Records (EHRs) system. The objective is to design and develop an innovative digital maternal health record system, overcoming the limitations of manual record-keeping. The scope includes login and registration modules, patient’s profiles, a digital Pink Book for health data recording, appointment scheduling, educational resources, and health summary reports. The expected results encompass a more organized and accessible maternal health record system, enhanced data accuracy, increased patient engagement, and reduced missed appointments. The methodology adheres to the waterfall approach, focusing on structured development phases, sequential progression, and milestone-based reviews. The application of this system is aimed at Malaysian maternal healthcare, contributing to a more efficient and sustainable healthcare system. The anticipated outcome is a user-friendly, tailored solution that meets the unique needs of healthcare providers and patients, ushering in a new era of digitalized maternal healthcare records.